Evaluation of a driving clinical decision pathway for generalist occupational therapists: Pilot test of practice change - Hayley M. Scott; Anne M. Baker; Carolyn A. Unsworth (Scandinavian Journal of Occupational Therapy)
Background Few evidence-based resources exist to support generalist occupational therapists address driving in practice. This pilot study aimed to evaluate whether a driving clinical decision pathway can assist generalist occupational therapists to address driving with clients.Methods Using a before (Timepoint-1) and after (Timepoint-2) design, data were collected at a multi-site outpatient community rehabilitation service. Medical record audits documenting how driving was addressed in practice and descriptive surveys of therapist’s perceptions of pathway use were collected at Timepoints 1 and 2. A driving clinical decision pathway was implemented over 6 months. Descriptive statistics and content analysis were used to analyse and compare data over time.Results Timepoint-1 data from 102 client medical records, and 13 clinician surveys were compared against Timepoint-2 data from 144 records and 8 surveys. Following implementation of the pathway, the number of assessments used by generalist occupational therapists increased three-fold, to inform driving process recommendations which increased two-fold. Clinicians’ self-reported knowledge, skills and confidence also increased two-fold.Conclusion A comprehensive driving clinical decision pathway provided clinicians with increased structure and support to guide practice change and promote role fulfilment in addressing return to driving with adults following a change in health status.